Using Electronic Money in Financial Transactions: Integrating the Second UTAUT Model - Prasetiyo, Yudhi (Accounting Department, Faculty of Economics and Business, Universitas Pembangunan Nasional Veteran Jawa Timur, 2023)
The use of digital or electronic money has become a trend in people's lives nowadays. Digital money payment systems make it easy to access transactions and even record transactions directly. The acceptance of technology, such as electronic money, in financial transactions was explored by integrating the second Unified Theory of Acceptance and Use of Technology (UTAUT) model. This research wants to know the behavior of using digital or electronic money in people's daily lives in carrying out financial transactions. This research provides an overview of exploratory observations using a quantitative approach. The primary data used to answer the phenomenon is data from a questionnaire. The target sample is a random population with a respondent age range of 17-55 years. IBM SPSS Statistics 25 and structural equation modeling (SEM) are the analytical tools used to identify and validate the elements and variables associated with the desire to conduct financial transactions using electronic or digital currency. There were 381 respondents from several large cities such as Medan, Jakarta, Bandung, Semarang, and Surabaya. The results of research on independent variables on behavior intention show there are four factors, of which there is a significant positive influence, namely performance expectations, social factors, facilitating conditions, and hedonic motivation; one variable has no effect, namely effort expectations. Then the price value and habit variables influence behavioral usage. Moreover, results from the intention variable also significantly impact behavioral usage.